The influence of high glucose concentration on the ability of mesenchymal stromal cells to stimulate blood vessel growth - Zhanna Alekseevna Akopyan; Georgy Vladimirovich Sharonov; Tatiana Nikolaevna Kochegura; Natalya Fedorovna Il'yashenko; Igor Eduardovich Belyanko; Valentina Ivanovna Dimitrova; Andrey Evgen'evich Zotikov; Natalya Igorevna Kalinina; Elena Viktorovna Parfenova (Сахарный диабет)
Adipose issue is a source of mesenchymal stem cells (MSC) that can be used to stimulate blood vessel growth in ischemic tissues. Various metabolicdisorders including hypeglycemia may have negative effect on therapeutic properties of these cells. Aim. To study the influence of high glucose concentration on functional activity in human adipose tissue. Materials and methods. Flow cytometry and real time PCR were used to study functional activity of cultured MSC from human adipose issue at highglucose concentration. Results. Prolonged (10-12 days) incubation at a high glucose concentration (25 mM) suppressed the ability of MSC to stimulate angiogenesis. Also,glucose modified expression of genes activating and inhibiting angiogenesis but had no effect on MSC proliferation and apoptosis. Conclusion. High glucose concentration suppresses angiogenic activity of MSC in adipose tissue; it may account for incomplete restoration of bloodflow in diabetic patients.